2017
DOI: 10.2196/mhealth.6309
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mobile Apps to Support the Care of Patients With Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundDiabetes Mellitus (DM) is a chronic disease that is considered a global public health problem. Education and self-monitoring by diabetic patients help to optimize and make possible a satisfactory metabolic control enabling improved management and reduced morbidity and mortality. The global growth in the use of mobile phones makes them a powerful platform to help provide tailored health, delivered conveniently to patients through health apps.ObjectiveThe aim of our study was to evaluate the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
234
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(251 citation statements)
references
References 47 publications
13
234
2
2
Order By: Relevance
“…In one metaanalysis, a decrease of 5 mm Hg in DBP or 10 mm Hg in SBP was found to reduce coronary heart disease events by 22% and stroke by 41% [47], as a decrease of 1 mm Hg in SBP leads to a 5% reduction in the risk of stroke [46]. The findings of this review are in line with other systematic reviews that involved smartphone and tablet based intervention in managing chronic diseases, which showed that the use of apps has the potential to improve health outcomes among those living with chronic diseases [8,10,11,49,50].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In one metaanalysis, a decrease of 5 mm Hg in DBP or 10 mm Hg in SBP was found to reduce coronary heart disease events by 22% and stroke by 41% [47], as a decrease of 1 mm Hg in SBP leads to a 5% reduction in the risk of stroke [46]. The findings of this review are in line with other systematic reviews that involved smartphone and tablet based intervention in managing chronic diseases, which showed that the use of apps has the potential to improve health outcomes among those living with chronic diseases [8,10,11,49,50].…”
Section: Discussionsupporting
confidence: 81%
“…Achieving an optimum level of self-management behaviour is difficult and requires considerable effort from patients. Mobile health technology (mHealth), defined as the use of mobile devices to deliver healthcare [7], has the potential to facilitate and optimise patients' self-management [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis of randomized controlled trials, published in March 2017, enrolled 1236 publications about the topic (59). A systematic review and meta-analysis of randomized controlled trials, published in March 2017, enrolled 1236 publications about the topic (59).…”
Section: Electronic Teaching and Applications For Smart Devicesmentioning
confidence: 99%
“…Areas of use include assistance in appointment-making, the monitoring of certain parameters in patients with chronic illnesses or the regular documentation of pain or other symptoms [3][4][5]. Initial experience for the use of mobile applications in the area of oncology has shown promising results: A prospective pilot trial was able to demonstrate significantly improved overall survival for lung cancer patients who were systematically telemonitored with the help of a mobile phone application based on patient-reported data and using the dynamics of patients' clinical symptoms for risk-stratification and individualized follow-up [6].…”
Section: Introductionmentioning
confidence: 99%